2017
DOI: 10.7124/bc.00095e
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epithelial-mesenchymal transition-related genes in prostate tumours

Abstract: To detect expression of EMT-related genes in prostate tumor samples and analyze a possible correlation between the gene expression level and clinical characteristics of prostate cancer in different groups. Methods. Expression of 19 genes was analyzed in 37 frozen samples of prostate cancer tissues at different tumor stages and Gleason scores, 37 paired conventionally normal prostate tissues and 20 samples of prostate adenomas, using quantitative PCR. Results. We have found that nine genes were expressed differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 34 publications
1
43
0
9
Order By: Relevance
“…[The] Clinicopathological characteristics (CPC) of adenocarcinomas and the presence and/or absence of the TMPRSS2/ERG fusion that was reported by us earlier [1,21] are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[The] Clinicopathological characteristics (CPC) of adenocarcinomas and the presence and/or absence of the TMPRSS2/ERG fusion that was reported by us earlier [1,21] are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Besides alteration of the expression pattern of the described seven genes, we found that the prostate-specific genes [19] and the tumor stromal elements [20] show differential expression in the tissues samples of prostate cancer, compared with the benign tumors. Also, the expression of genes, involved in EMT was altered [21], and in a proportion of prostate tumors the presence of the TMPRSS2:ERG fusion was detected [22].…”
Section: Introductionmentioning
confidence: 99%
“…All samples were collected in accordance with the Declaration of Helsinki and the guidelines, issued by an Ethic Committee of the Institute of Urology of National Academy of Medical Sciences of Ukraine and of the National Cancer Institute of National Academy of Sciences of Ukraine (NASU), and the Ethic Committee of the Institute of Molecular biology and genetics of NASU. Experimental studies were conducted, using 37 prostate adenocarcinoma samples of different Gleason scores and at various stages; 37 corresponding conventional normal tissue (CNT) samples; and 20 samples of adenomas [10,11]. The tumor samples were characterized, according to the International System of Classification of Tumors, based on the tumor-node-metastasis (TNM) and the World Health Organization (WHO) criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The tumor samples were characterized, according to the International System of Classification of Tumors, based on the tumor-node-metastasis (TNM) and the World Health Organization (WHO) criteria. The clinical characteristics of the tumors were described earlier [10,11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation